UNCERTAINTY MODELLING OF CITIZEN-CENTERED GROUP DECISION MAKING USING FUZZY-VIKOR CASE STUDY: SITE SELECTION OF HEALTHCARE SERVICES - Z. Neisani Samani; A. A. Alesheikh (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
The participation of citizens in decision-making processes is one of the main concerns in urban planning. People’s contributions increase the usability and efficiency of urban facilities. Hospitals and healthcare services are among the most important public facilities that citizens require. This paper aims to improve an approach that could locate the hospitals according to the citizens’ preferences. Decision-making process in this situation should consider the uncertainties exist in any steps of decisions-making. In this regard, this paper applied Fuzzy-VIKOR method that is appropriate to model such kind of uncertainty. The proposed method was accomplished in Districts 6 of Tehran province. The achieved results were compared with each other in two different scenario (using expert knowledge and citizens’ satisfaction). The comparison of the results showed that the more suitable distribution and density of proposed sites for hospitals must be observed if the citizens’ perspectives were considered. Also, the proposed sites with experts follow urban planning principals rather than the second case.